2015
DOI: 10.1177/0018720815609503
|View full text |Cite
|
Sign up to set email alerts
|

Boredom in the Workplace

Abstract: Personnel selection and improvements in system and task design can potentially mitigate boredom. However, more work is needed to develop and evaluate other potential interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(55 citation statements)
references
References 157 publications
(173 reference statements)
2
41
0
7
Order By: Relevance
“…We observed that these correlations were particularly pronounced during the medium and high traffic volumes and less strong for the low-traffic volume. During the latter, requirements were very low and allowed air traffic controllers to have task-unrelated thoughts in order to cope with boredom (Cummings et al, 2015). Boredom proneness, coping strategy as well as the kind of task-unrelated thoughts could have mitigated the correlation between the two 25 ac/h scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that these correlations were particularly pronounced during the medium and high traffic volumes and less strong for the low-traffic volume. During the latter, requirements were very low and allowed air traffic controllers to have task-unrelated thoughts in order to cope with boredom (Cummings et al, 2015). Boredom proneness, coping strategy as well as the kind of task-unrelated thoughts could have mitigated the correlation between the two 25 ac/h scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…MW might actually help to cope with boredom (Schooler et al, 2014). Boredom arises when people are unable to engage in satisfying activities while blaming their environment for it (Cummings et al, 2015). Several studies by Cheyne et al (Cheyne et al, 2006; Carriere et al, 2008) point to the relationship between MW and boredom.…”
Section: Mind Wandering To Complete Ootl Theoriesmentioning
confidence: 99%
“…Using questionnaires, they found a significant increase in everyday attentional failures for individuals more prone to boredom. Interestingly, Cummings et al (2015) recently warned about a possible increase in boredom when integrating higher levels of automation. Moreover, MW related to automation was recently observed in automated systems.…”
Section: Mind Wandering To Complete Ootl Theoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…(Chen et al, 2006). Other significant incentives include collegiality in decision-making, provision of internal communications and abundant research resources (Liu, & Perry, 2016;Cummings et al, 2016;Bharadwaj, 2014;Becerril-Ángel et al 2017). …”
Section: Introductionmentioning
confidence: 99%